The Crime of Evading the Enforcement of a Compensatory Measure in the Amendment to the Criminal Code - Wilk, Leszek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The article refers to the issue of the amendment to the Criminal Code, introducing a new crime of evading the enforcement of a compensatory measure ordered by the court. Pursuant to this provision, a person who evades the enforcement of a compensatory measure in the form of an obligation to repair damage or compensation for harm or indemnity for an offense prosecuted by the public indictment, ordered by the court in favor of the injured party or a person closest to him / her, is subjected to the imprisonment penalty. It is therefore worth considering whether the amendment in question is needed, and what the consequences of its introduction may be.